PENGARUH CORPORATE GOVERNANCE TERHADAP PERINGKAT OBLIGASI PERUSAHAAN (Studi Empiris atas Obligasi Perusahaan yang Terdaftar di BEI Periode 2008-2011) - , BOGY ARIYANTO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to examine the influence of Corporate Governance of corporate bond ratings. Corporate Governance is measured by the size of the board of commissioners, the proportion of independent commissioners, the proportion of blockholdingâs share, managerial ownership, and audit committee expertise toward the company's bond rating that listed on Indonesia Stock Exchange period 2008-2012 with the leverage and return on asset (ROA) as a controlling variable. The bond rating uses credit ratings that issued by Pemeringkat Efek Indonesia (Pefindo). Sample uses companyâs bond listed on the Indonesia Stock Exchange (IDX) with periods of observation 2008, 2009, 2010, and 2011. Sample selection uses Purposive Sampling method. Using Ordinary Least Square (OLS), the research results that board of commissionerâs size and managerial ownership have significantly influence to corporate bond ratings.